The Sheffield experiment: the effects of centralising accident and emergency services in a large urban setting. Issue 3 (1st May 2001) - Simpson, A N; Wardrope, J; Burke, D
Abstract : Objectives —To assess the effects of centralisation of accident and emergency (A&E) services in a large urban setting. The end points were the quality of patient care judged by time to see a doctor or nurse practitioner, time to admission and the cost of the A&E service as a whole. Methods —Sheffield is a large industrial city with a population of 471 000. In 1994 Sheffield health authority took a decision to centralise a number of services including the A&E services. This study presents data collected over a three year period before, during and after the centralisation of adult A&E services from two sites to one site and the centralisation of children's A&E services to a separate site. A minor injury unit was also established along with an emergency admissions unit. The study used information from the A&E departments' computer system and routinely available financial data. Results —There has been a small decrease in the number of new patient attendances using the Sheffield A&E system. Most patients go to the correct department. The numbers of acute admissions through the adult A&E have doubled. Measures of process efficiency show some improvement in times to admission. There has been measurable deterioration in the time to be seen for minor injuries in the A&E departments. This is partly offset by the very good waiting time to be seen in the minor injuries unit. The costs of providing the service within Sheffield have increased. Conclusion —Centralisation of A&E services in Sheffield has led to concentration of the most ill patients in a single adult department and separate paediatric A&E department. Despite a greatly increased number of admissions at the adult site this change has not resulted in increased waiting times for admission because of the transfer of adequate beds to support the changes. There has however been a deterioration in the time to see a clinician, especially in the A&E departments. The waiting times at the minor injury unit are very short.